Attracting safe employees: How job adverts can affect applicants' choices. (February 2015) - Fruhen, L.S.; Weis, L.M.; Flin, R.
Highlights: Can organisations attract employees with attributes known to be related to safe behaviour through job adverts? Participants evaluated two job adverts and reported their safety attitude, promotion- and prevention focus and pessimism. Safety attitude was positively related to the attraction of the safety focussed job and promotion focus to both jobs. Prevention focus and pessimism were not found to clearly relate to applicant choices. Abstract: It is not known how organisations in high risk contexts can attract employees with personal attributes that are likely to support organisational safety. Using questionnaires ( n  = 179), we investigated whether explicit prioritisation of safety in job adverts influences attraction to an organisation based on individuals' safety attitude, prevention–promotion focus and pessimism. Individuals with a more positive safety attitude rated the safety-focussed company as attractive and rejected the business-focussed company. Prevention focus, did not relate to attraction to either of the companies. However, a more pronounced promotion focus in individuals was associated with a positive perception of both jobs, indicating that the desire to get a job might be an overriding factor. Furthermore, pessimism did not clearly relate to participants' preferences of the two job adverts. The results suggest that attracting applicants that hold safety related attributes might take more than highlighting safety in job adverts and requires conveying a real sense of commitment to safety and consideration of the management of risks.